The Dialect of the Tribe: Interviewing Highly Experienced Writers to Describe Academic Literacy Practices in Business Studies - Cain, Liz; Pople, Ian (Journal of Academic Writing, 2011)
Much recent discussion of ‘academic literacies’ has focussed upon the ways in which students are accultured into appropriate discourses and genres in the academy. This may be particularly true where a discipline has a very strong sense of lexicon and content. In awareness of this, semi-structured interviews were carried out in the spring of 2009 with three highly experienced academic writers in the department of Accounting and Finance at the Manchester Business School. The main focus of this paper is on academic literacy practices. The results of the interviews are discussed in this paper, which examines the relationship between experienced writers and their discourse community, the norms within which they work, the place for creativity, and the extent to which each of these may be negotiated. It will firstly consider the concepts of ‘discourse community’ and ‘Community of Practice’ (CoP), before discussing notions of creativity and ideas-generation as a means of informing the academic work that these writers develop.